Facial paralysis due to a spitting cobra bite. (September 2021) - Rinkel, Willem D.; Mastenbroek, Richard; Wismans, Pieter J.; Mureau, Marc A.M.
Summary: The global burden of snakebites is growing, particularly its nonfatal sequelae. Therefore, the World Health Organization reinstated snakebites to its list of Neglected Tropical Diseases. We describe the case of a 4.5-year-old boy who was bitten by a spitting cobra, resulting in considerable local swelling accompanied by a right-sided facial paralysis due to neurotoxicity by cobra venom. Presently, surgical methods to recover facial paralysis include nerve repair, nerve grafting, nerve transfers, static slings, muscle transfers, and functional muscle transplantations. However, mime therapy consisting of neuromuscular retraining resulted in a good functional result with a moderate contour deficiency of the right cheek and a subtle paresis of the zygomatic muscles at 1 year and 9 months follow-up. The natural history of facial paralysis in our case shows that this condition can be transient and may resolve with mime therapy as a conservative measure.